Keanekaragaman Ngengat Superfamily Bombicoidea: Eksplorasi Potensi Ulat Sutera di Dataran Rendah Kabupaten Jayapura - Hendra K. Maury; Marsi A. Purwadi; Euniche R.P.F. Ramandey; John R. Bisai; Bruce H.R. Mauri (Jurnal Biologi Papua, 2022)
Jayapura Regency is one of the regions that considerable potential for economic growth from non-timber forest products. In the development of non-timber forest products in the form of products produced by insects, silk yarn is one of the commodity that has a high demand. The domestic demand for silk yarn is 900 tons/year, while only 19.05 tons/year were produced in 2012. Jayapura Regency has a great potential to supply the shortage of cocoon for the domestic market and the wide open international market. Related to this challenge, this study conducted basic research on the diversity of moths from the Bombicoidea superfamily in the natural forest of Kampung Soaib, Jayapura Regency. Sampling using light traps, four species of moths from the Saturnidae family were obtained, Syntherata apicalis, Opodiphtera intermedia, Opodiphtera papuana, and Coscinocera hercules. The cocoon of Coscinocera hercules is very potential as a silk thread producer because it is large and consists of two layers with brown color and has fiber characteristics similar to the cocoon of Attacus atlas which has been developed as a wild silk producer. These results indicate that the lowland forests of Jayapura Regency as a habitat for wild silkworm species has potential to be developed as non-timber forest products.Key words: Superfamily Bombicoidea; silkworm; cocoon; Jayapura regency